640 A case series on recurrent and persisting IgA vasculitis in children. (17th August 2022) - Marro, Julien; Williams, Chloe; Wadden, Louise; Pain, Clare; Oni, Louise
Abstract : Aims: Up to 30% of children with IgA vasculitis (IgAV; previously Henoch-Schönlein Purpura) will experience at least one relapse of the disease, sometimes months or even years after the initial presentation. Those cases pose a diagnostic and therapeutic challenge to clinicians due to the lack of consensus on classification and treatment of recurrent and persisting IgAV. 1 The aim of this retrospective case series was to describe a cohort of children diagnosed with either recurrent or persisting IgAV. Methods: Children with a diagnosis of recurrent or persisting IgAV followed-up within the last 5 years at Alder Hey Children's Hospital (Liverpool, UK) were included in this case series. Recurrent or persisting disease was defined if it had been stated in a clinical letter by a paediatric rheumatologist or nephrologist. Clinical data was retrospectively collected from medical notes. Systematic literature reviews were conducted in line with PRISMA guidance to identify existing definitions for recurrent and persisting IgAV in children. Results: 13 children met the inclusion criteria. Median age at first presentation was 10.2 years [2.6-15.5], female:male ratio was 1.2:1 and median follow-up was 57.7 months [14.3-165.7]. Recurrent disease was diagnosed in 4 children and persisting in 9. All children presented with a purpuric rash (either recurring or persisting), however the main symptom prompting referral was arthralgia (n=9). 8 children were treated with disease-modifying antirheumatic drugs (DMARDs). The median time from first presentation to diagnosis was 18.4 months [5.3-150.8] and the time from first presentation to treatment (PTT) with DMARDs was 24.1 months [1.8-95.4]. Children with renal involvement were treated more promptly with DMARDs (n=3; PTT – 8.1 months [1.8-24.5]) than those without nephritis (n=5; PTT - 35.3 months [21.6-95.4]). 8 children were admitted at least once over the course of their disease and 10 re-presented at least once to A&E. Further details are shown in table 1 . The systematic reviews identified 40 records providing definitions for recurrent (n=31), persisting (n=5) IgAV or both (n=4). 'Recurrent' disease was most commonly defined in the literature as a new onset of purpura alongside any other characteristic signs of IgAV 4 weeks after achieving complete remission and 'persisting' was defined as a typical purpuric rash alongside other symptoms lasting over 1 month. Conclusion: There is no universally agreed definition of recurring/persisting IgAV and this may contribute to a delay from first presentation to diagnosis and/or treatment. This case series emphasises the need for standardised definitions to enable better management for children with an atypical disease course. Reference: Reamy BV, Servey JT, Williams PM. Henoch-Schönlein Purpura (IgA Vasculitis): Rapid Evidence Review. Am Fam Physician (2020)